Recent Advances and New Challenges: Two-Dimensional Metal–Organic Framework and Their Composites/Derivatives for Electrochemical Energy Conversion and Storage. (13th February 2023) - Nivetha, Ravi; Sharma, Sushant; Jana, Jayasmita; Chung, Jin Suk; Choi, Won Mook; Hur, Seung Hyun
Abstract : Metal–organic frameworks (MOFs), as a new generation of intrinsically porous extended crystalline materials formed by coordination bonding between the organic ligands and metal ions or clusters, have attracted considerable interest in many applications owing to their high porosity, diverse structures, and controllable chemical structure. Recently, 2D transition-metal- (TM-) based MOFs have become a hot topic in this field because of their high aspect ratio derived from their large lateral size and small thickness, as well as the advantages of MOFs. Moreover, 2D TM-based MOFs can act as good precursors to construct heterostructures with high electrical conductivity and abundant active sites for a range of applications. This review comprehensively introduces the widely adopted synthesis strategies of 2D TM-based MOFs and their composites/derivatives. In addition, this paper summarizes and highlights the recent advances in energy conversion and storage, including the hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, CO2 reduction reaction, urea oxidation reaction, batteries, and supercapacitors. Finally, the challenges in developing these intriguing 2D layered materials and their composites/derivatives are examined, and the possible proposals for future directions to enhance the energy conversion and storage performance are reviewed.